Weighted-sum-of-gray-gases models for non-gray thermal radiation of hydrocarbon fuel vapors, CH4, CO and soot. (October 2021) - Sadeghi, Hosein; Hostikka, Simo; Fraga, Guilherme Crivelli; Bordbar, Hadi
Abstract: Using the high-resolution experimental spectral absorption coefficients of six fuel gases and the line by line absorption spectra of CO and CH4 based on HITRAN and HITEMP spectral databases, in this paper, novel coefficients for weighted-sum-of-gray-gases (WSGG) model are presented for Heptane, Methane, Methanol, MMA, Propane, Propylene, Toluene, and CO. Moreover, for soot, the spectral absorption coefficients were calculated assuming Rayleigh regime implementing the complex index of refraction obtained from the correlations of Chang and Charalampopoulos. The presented WSGG models were coupled with those of literature for CO2 and H2 O by means of the superposition method. The models were first validated in several one-dimensional benchmarks representing various levels of inhomogeneous conditions in temperature, gas concentration and soot loading. Then, the WSGG models were employed in solving a three-dimensional case representing a Heptane pool fire. Using the time averaged 3-D CFD profiles, the WSGG models solved the spectral radiative heat transfer exhibiting excellent agreement with the results of line by line calculations in terms of radiative heat flux and radiative heat source. Moreover, the emissivity charts were provided comparing the emissivity calculated by LBL calculations with those of the new WSGG models.